Peningkatan Pendidikan Reproduksi pada Anak Disabilitas Intelektual - Efi Kristiana; Erni Yuliastuti; Suryanti (Rena Cipta Mandiri, 2025)
Children with intellectual disabilities are often subjected to violence because their intellectual limitations prevent them from realizing that they have undergone physical changes, so they do not mind when other people touch them. The results of a needs assessment conducted by Rutgers WPF Indonesia together with the Directorate of PKLK Development of the Ministry of Education and Culture in 2017 in three provinces in Indonesia showed that adolescents with intellectual disabilities have low knowledge about the concepts of women and men, puberty, pregnancy, healthy relationships, and protection from sexual violence. Sexual violence against persons with disabilities is a serious problem in Indonesia, including in Banjar Regency. The purpose of this community service is to provide an understanding of reproductive health using magnetic crossword puzzle boards and Flip Chat at SLB N 2 Martapura. With increased knowledge and understanding, children with disabilities can identify actions that should not be done to them by others. The results of this community service program indicate that improving reproductive education for children with intellectual disabilities through the pre-test and post-test method is effective in enhancing their knowledge. The pre-test results showed that only 4 respondents (13%) had good knowledge, while in the post-test, this number increased to 20 respondents (67%). This improvement helps the children understand how to behave and act assertively to protect themselves, as well as encourages them to seek help immediately if they encounter any indication of a crime directed at them.